PERANCANGAN APLIKASI HUMAN RESOURCES DEVELOPMENT (HRD) PADA VIZTA GYM MENGGUNAKAN METODE DELONE AND MCLEAN - Wijaya, Robby; Aryanto, Didik; David, David (Majalah Ilmiah METHODA, 2024)
This research aims to develop a Human Resources Development (HRD) application for Vizta Gym, a fitness center with four branches in the city of Medan. Currently, the company is still facing problems in managing Human Resources (HR) because it uses a manual recording system. Data integration between branches is less effective, making it difficult to record jobs and obtain information about employee conditions and performance. Complicated employee data management also causes errors in data management. The process of calculating employee salaries is also slow and has the potential for errors to occur. The HRD application that was built has an automatic salary calculation feature based on employee absences, leave, permission, illness, holidays, tardiness, and absence. With this application, HR management can monitor employee performance and calculate salaries quickly and accurately. Automatic reporting features, including payroll slips and employee salary summary, are also provided. The results showed that the HRD application was successful in overcoming complex employee data management problems at Vizta Gym. The DeLone and McLean method was used to measure the success of this application and showed very good results with percentages above 85% for each indicator variable.